2017
DOI: 10.21608/avmj.2017.170959
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis in Small Ruminants Slaughtered in Aswan Slaughterhouse, Egypt

Abstract: The aim of the present study was to determine the prevalence, organ distribution, morphological characters and economic importance of Cysticercus ovis and Cysticercus tenuicollis in sheep and goats. A total of 669 sheep and 484goats slaughtered at Aswan Slaughterhouse were carefully examined for these metacestodes. Cysticercus ovis was detected (1.94%) from slaughtered sheep. Cysticercus tenuicollis was found (13.3%) in sheep and (24.2%) in goats. The prevalence of both C.ovis and C.tenuicollis was higher in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…However, some studies have reported a signi cantly higher prevalence of T. hydatigena infection in females (Khanjari et al 2015), which may be due to females being kept in the herd longer than males (Mirzaei and Rezaei 2015). Cysts were mainly found in the omentum, mesentery, liver, and spleen, which is consistent with previous ndings (Dyab et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…However, some studies have reported a signi cantly higher prevalence of T. hydatigena infection in females (Khanjari et al 2015), which may be due to females being kept in the herd longer than males (Mirzaei and Rezaei 2015). Cysts were mainly found in the omentum, mesentery, liver, and spleen, which is consistent with previous ndings (Dyab et al 2017).…”
Section: Discussionsupporting
confidence: 89%